2022
DOI: 10.3390/agronomy12020319
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Bunch Detection in White Grape Varieties Using YOLOv3, YOLOv4, and YOLOv5 Deep Learning Algorithms

Abstract: Over the last few years, several Convolutional Neural Networks for object detection have been proposed, characterised by different accuracy and speed. In viticulture, yield estimation and prediction is used for efficient crop management, taking advantage of precision viticulture techniques. Convolutional Neural Networks for object detection represent an alternative methodology for grape yield estimation, which usually relies on manual harvesting of sample plants. In this paper, six versions of the You Only Loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 58 publications
(76 reference statements)
3
89
0
2
Order By: Relevance
“…For this purpose, their model reached an inference time of only 12 ms per image on an Nvidia GTX 1050Ti GPU. Similarly, a counting error of 13.3% was reported in the work of Sozzi et al [112] with a Yolov5x model. The performance obtained by Aguiar et al [94] seems to be closer to the natural condition of many vineyards: their SSD-MobileNet model reached 49.85 and 53.34% mAP on grapes before veraison, without defoliation, and at two different phenological stages.…”
Section: Performance Comparisonsupporting
confidence: 67%
“…For this purpose, their model reached an inference time of only 12 ms per image on an Nvidia GTX 1050Ti GPU. Similarly, a counting error of 13.3% was reported in the work of Sozzi et al [112] with a Yolov5x model. The performance obtained by Aguiar et al [94] seems to be closer to the natural condition of many vineyards: their SSD-MobileNet model reached 49.85 and 53.34% mAP on grapes before veraison, without defoliation, and at two different phenological stages.…”
Section: Performance Comparisonsupporting
confidence: 67%
“…While many previous studies have focused on berry counting, some have examined bunch detection using the YOLO model. Sozzi et al [21] demonstrated an AP value of 0.76 with YOLOv5. However, grape bunches visualized in the study appear in higher resolution, with less occlusion than seen in the present work.…”
Section: Saliency Mapping and Model Visualizationmentioning
confidence: 97%
“…Much of the previous work has been performed in orchard crops, such as apples [11,14], oranges [15], and mangos [16]. Studies in other specialty crops, including tomatoes [9,17] and grapes [18,19,20,13,21] have also been conducted. In vineyards, much of the existing literature in yield estimation from proximal imagery have consisted of methods leveraging feature engineering and computer vision to count individual grape berries [22,2,23], although pixel count has also been related to grapevine yield [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deep neural network is utilized to build the predictive model. DNN is an artificial neural network (ANN) algorithm with several hidden layers [30,31]. The proposed DNN model in this paper has four hidden layers.…”
Section: Deep Learningmentioning
confidence: 99%